Clinical outcomes of 10years of cardiac screening in elite New Zealand athletes - Orchard, J. J.; Orchard, J. W.; Davis, A. J.; Puranik, R.; Isbister, J. C.; La Gerche, A.; Driscoll, T.; Doughty, R. N.; Hamilton, B. (Journal of Science and Medicine in Sport, 2023)
Objectives To report findings from the High Performance Sport New Zealand cardiac screening programme, including comparisons between sexes and ethnicities.